2010
DOI: 10.3171/2010.1.focus09263
|View full text |Cite
|
Sign up to set email alerts
|

Complications and radiographic correction in adult scoliosis following combined transpsoas extreme lateral interbody fusion and posterior pedicle screw instrumentation

Abstract: Object The authors recently used a combined approach of minimally invasive transpsoas extreme lateral interbody fusion (XLIF) and open posterior segmental pedicle screw instrumentation with transforaminal lumbar interbody fusion (TLIF) for the correction of coronal deformity. The complications and radiographic outcomes were compared with a posterior-only approach for scoliosis correction. Methods The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
180
4
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(209 citation statements)
references
References 25 publications
11
180
4
4
Order By: Relevance
“…In a review summarizing 18 studies with a total of 2310 patients, 304 patients had complications related to lumbar plexus injury representing a 13% risk [2] despite intraoperative neuromonitoring. Although many of these complications were reported as transient, persisting neurologic symptoms might occur in different intensity in as much as 18% [15,25,33,46]. Because the access corridor is transmuscular for this technique, intramuscular preparation is likely the main underlying reason for the abovedescribed nerve root injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review summarizing 18 studies with a total of 2310 patients, 304 patients had complications related to lumbar plexus injury representing a 13% risk [2] despite intraoperative neuromonitoring. Although many of these complications were reported as transient, persisting neurologic symptoms might occur in different intensity in as much as 18% [15,25,33,46]. Because the access corridor is transmuscular for this technique, intramuscular preparation is likely the main underlying reason for the abovedescribed nerve root injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with neuromonitoring there is a high risk of approach-related neurologic and muscular complications. The risk of postoperative hip flexor and quadriceps weakness, which are considered to be approach-related muscular trauma, range between 20% and 36%, whereas sensory deficits and anterior thigh pain range between 25% and 75% and 23% and 60%, respectively [15,20,25,33,43,46].…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons have theorized that this may be related to direct cutaneous nerve neuropraxia or an indirect mechanism via a psoas muscle inflammatory response due to mechanical dissection. The incidence of this varies considerably in the literature from 1 to 75% [2,[10][11][12]. Several studies have reported on post-operative neurologic deficits following LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…However, the determination of absolute prevalence of deficits and their natural history as well as contributing factors remains incomplete and controversial in the literature. Overall, the number of postoperative neurologic events ranges in literature between 0.6 and 33.6% after LLIF [10,11,[13][14][15][16]. In a study by Tohmeh et al [12] 28% of patients experienced a new iliopsoas weakness and 18% claimed of sensory loss at the upper medial thigh although intra-operative real-time monitoring was used to prevent neurologic deficits after LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…The average reported followup ranged from 2 days to 24 months [7, 12-16, 20, 26, 27, 32-34, 36]. VAS pain score, reported in eight of 13 studies, improved on average from 8.3 to 3.6, and ODI, reported in five of 13 studies, improved on average from 48.1 to 27.3 [7,13,14,16,20,27,32,34,36].…”
Section: Discussionmentioning
confidence: 99%